THE EFFECT OF AGENCY COSTS, OWNERSHIP STRUCTURE, SIGNALING, INVESTMENT OPPORTUNITIES, SIZE, FINANCIAL LEVERAGE, AND PROFITABILITY ON DIVIDEND POLICY OF COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE - Ferdi Nusaputra; Sautma Ronni Basana (Finance and Investment Program, School of Business and Management - Petra Christian University, 2020)
The purpose of this research is to determine the effect of agency cost, ownership structure, signaling, investment opportunities, size, financial leverage, and profitability on dividend policies on public companies listed on the Indonesian Stock Exchange (IDX) period 2014 - 2019. This research sample uses the entire list of companies listed on the Indonesian Stock Exchange period 2014 - 2019. The data analysis method used is tobit regression. The results of this research analysis suggest that agency cost, ownership, investment opportunities, size, financial leverage, and profitability have a significant effect on dividend policy on companies listed in IDX period 2014 - 2019.